2020
DOI: 10.1155/2020/6946037
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Improves Autophagy of Aged Hepatocytes via Increasing Telomerase Activity in Liver Injury

Abstract: An aged liver has decreased reparative capacity during ischemia-reperfusion (IR) injury. A recent study showed that plasma irisin levels predict telomere length in healthy adults. The aim of the present study is to clarify the role of irisin, telomerase activity, and autophagy during hepatic IR in the elderly. To study this, hepatic IR was established in 22-month- and 3-month-old rats and primary hepatocytes were isolated. The results showed that the old rats exhibited more serious liver injury and lower level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 43 publications
7
50
0
Order By: Relevance
“…Moreover, it was shown that normal physiological aging could be delayed without increasing the incidence of cancer, as demonstrated in adult wild-type mice (pharmacological activation or systemic viral transduction of telomerase) [31,32]. As shown in an old rat model, telomerase induction mediated by irisin (a secreted myokine) was accompanied by autophagy induction and improved mitochondrial function in aged hepatocytes [33]. Another telomerase activator, TA-65 (extracted from Astragalus Membranaceus) that is capable of increasing average telomere length and decreasing the percentage of critically short telomeres, was studied in a mouse model.…”
Section: (Re)activation Of Telomerasementioning
confidence: 99%
“…Moreover, it was shown that normal physiological aging could be delayed without increasing the incidence of cancer, as demonstrated in adult wild-type mice (pharmacological activation or systemic viral transduction of telomerase) [31,32]. As shown in an old rat model, telomerase induction mediated by irisin (a secreted myokine) was accompanied by autophagy induction and improved mitochondrial function in aged hepatocytes [33]. Another telomerase activator, TA-65 (extracted from Astragalus Membranaceus) that is capable of increasing average telomere length and decreasing the percentage of critically short telomeres, was studied in a mouse model.…”
Section: (Re)activation Of Telomerasementioning
confidence: 99%
“…Irisin is a soluble peptide cleaved from the extracellular domain of FNDC5, regulating the apoptotic program or autophagic reaction in various cell types [23,32]. The analyses of decreased FNDC5 signaling in osteoarthritic chondrocytes in human OA prompted us to isolate Irisin recombinant proteins and verify whether the gained Irisin function changed knee OA development.…”
Section: Irisin Attenuated Articular Cartilage Loss and Irregular Gaimentioning
confidence: 99%
“…Recently, several studies indicated that autophagy is substantially lower in the aged liver compared to the young liver [5,[14][15][16]. Aging leads to a decrease in the number and function of autophagosomes and causes lipofuscin accumulation.…”
Section: Aging Impairs Autophagymentioning
confidence: 99%